PENINGKATAN AKTIVITAS DAN HASIL BELAJAR ILMU PENGETAHUAN SOSIAL MENGGUNAKAN MODEL KOOPERATIF TIPE STAD KELAS IV - Nego, Julius Abed (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This research aims to determine whether an increase in the activity and results of student learning in a learning model cooperative type using IPS student team achievement division in class IV elementary school the country 35 South Pontianak. The research method used is descriptive method with the class action research. Subject research 34 students. The research results obtained are the cycle I, i.e. the ability of the teachers carry out a study on cycle I with an average score of 3.01, cycle II 3.30, and cycle III 3.74. While the learning activities of students in cycle I of 50,30%, cycle II 67.05% and cyclical III 78,23%. Student learning outcomes at the initial data with average 67.5, cycle I of 73.48, cycle II of 76.91 and cycle III of 81.62 cooperative model means the type of student team achievement division can improve the activity and results of student learning. Keywords: Activity And Learning, Learning Outcomes, IPS, Cooperative Model Type Student Team Achievement Division